Layered structures of assembled imine-linked macrocycles and two-dimensional covalent organic frameworks give rise to prolonged exciton lifetimes. Issue 8 (26th January 2022) - Helweh, Waleed; Flanders, Nathan C.; Wang, Shiwei; Phelan, Brian T.; Kim, Pyosang; Strauss, Michael J.; Li, Rebecca L.; Kelley, Matthew S.; Kirschner, Matthew S.; Edwards, Dillon O.; Spencer, Austin P.; Schatz, George C.; et al.
Abstract : Excitonic dynamics studies of a 2D COF, its corresponding hexagonal macrocycle, and extended nanotubes comprised of stacked macrocycles reveal that layering of the macrocycle in the assembled COF and nanotube lead to a prolonged exciton lifetime. Abstract : Ordered organic materials and assemblies have great potential to be tailored to have desirable properties for optoelectronic applications, such as long exciton lifetime and high directional exciton mobility. Framework materials, such as two-dimensional covalent organic frameworks (2D COFs), as well as their truncated macrocyclic analogues, are versatile platforms to organize functional aromatic systems into designed assemblies and robust materials. Here we investigate the exciton dynamics in a 2D COF, its corresponding hexagonal macrocycle, and extended nanotubes comprised of stacked macrocycles. The excitonic behavior of these three systems provide an understanding of excitonic processes that occur in the plane of the covalently bonded 2D macromolecules and between layers of the nanotubes and 2D COF. The nanotube and analogous 2D COF exhibit longer excited-state lifetimes (∼100 ps) compared to the individual, solvated macrocycles (<0.5 ps). These differences are attributed to the internal conversion facilitated by the internal motions of the imine linkages which are significantly reduced in the assembled macrocycles in the nanotube and 2D COF sheets in the layered structures. The exciton diffusion processes in the assembled nanotubes and 2D COF systems were characterized by the autocorrelations of the transition dipole moment of the excitons, giving the depolarization time constants for both systems to be ∼1 ps. This work also reveals the anisotropic exciton dynamics related to the in-plane and inter-plane structural factors in these systems. These studies provide guidance for the design of future COF materials, where the longer excited state lifetimes imparted by assembly are beneficial for optoelectronic applications.